CAR T-cells therapy as a ray of hope for cancer treatment - Chopra, Hitesh; Chopra, Shivani; Arora, Sonia; Dhama, Kuldeep (Trends in Immunotherapy, 2024)
New hope for patients with specific blood malignancies has arisen with the emergence of chimeric antigen receptor (CAR) T-cell therapy as a revolutionary approach to cancer immunotherapy. This groundbreaking therapy modifies a patient’s immune system such that their own T cells can identify and destroy cancer-specific antigens by expressing CARs. Multiple myeloma, lymphomas, and leukemias are among the blood malignancies that have been treated with six CAR T-cell treatments that have been approved by the FDA since 2017. The treatment entails drawing T cells out of the patient’s blood, changing their genes to produce CARs, and then reintroducing these modified cells into the patient. The CAR T-cells have the ability to identify cancer cells, proliferate, and kill them once they enter the circulation. This might lead to long-term protection from the illness. Patients with blood malignancies who have relapsed or are resistant to previous treatments have shown encouraging results in clinical studies, with some patients even managing to achieve long-term remissions. Cytokine release syndrome and neurological toxicities are two of the many potential adverse effects of CAR T-cell treatment that must be carefully managed. The complicated production method and expensive treatment cost further restrict its broad availability. Research is ongoing with the goals of improving the safety profile, increasing the effectiveness, and expanding the applicability of CAR T-cell therapy to solid tumors.